2008
DOI: 10.1007/s00015-008-1250-8
|View full text |Cite
|
Sign up to set email alerts
|

Dimerelloid rhynchonellide brachiopods in the Lower Jurassic of the Engadine (Canton Graubünden, National Park, Switzerland)

Abstract: New brachiopods (Dimerelloidea, Rhynchonellida) from Lower Jurassic (?lower Hettangian) hemipelagic sediments of the Swiss National Park in south-eastern Engadine are described: Sulcirostra doesseggeri sp. nov. and Carapezzia engadinensis sp. nov. Sulcirostra doesseggeri is externally similar to S. fuggeri (FRAUSCHER 1883), a dubious species, that could not be included in a comparative study, because relevant samples no longer exist. A single specimen was tentatively assigned to Sulcirostra ?zitteli (BÖSE 1894… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Shells and other skeletal elements of dead organisms were transported into the neighbouring basin together with loose sediment. The submarine high was approximately 100 metres below sea level or even deeper, given the total absence of phototrophic organisms such as corals or algae, and the surrounding basin was probably several hundred metres deep (SULSER & FURRER 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shells and other skeletal elements of dead organisms were transported into the neighbouring basin together with loose sediment. The submarine high was approximately 100 metres below sea level or even deeper, given the total absence of phototrophic organisms such as corals or algae, and the surrounding basin was probably several hundred metres deep (SULSER & FURRER 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, the Alpisella beds, deposited just above the megabreccias are tilted, but not folded blocks of Upper Triassic carbonates and do not show tectonic deformation. The effects of deformation are also absent from brachiopods found in the same beds as the crustaceans (SULSER & FURRER 2008) and in the crustaceans themselves the appendages of the cephalothorax do not appear to have been deformed significantly in any particular direction. Therefore, it is likely that the original shape of the new form is preservedand that it was undoubtedly narrow.Although the margins of the cephalothoracic shield are poorly preserved, several small antrorse spines are observed that often occur on the lateral margin in other polychelidan lobsters, suggesting the margins in this specimen to be complete and not damaged during either the fossilisation process or subsequent preparation.…”
Section: Remarksmentioning
confidence: 93%
See 1 more Smart Citation
“…bivalves, echinoderms, or brachiopods) is mostly very low (operationally, no or very few skeletal remains encountered along 5 m-long bed transects), implying the presence of conditions that were limiting calcimass production by macroinvertebrates. Beds with relatively frequent bivalves, echinoderms, or brachiopods occur but are rather scarce at outcrop and formation scales (Gaździcki et al 1979;Sulser & Furrer 2008) and skeletal-rich deposits are absent in the spotted deposits. However, this paradox and the causes of the paleocommunity structure that characterizes spotted deposits are poorly explored (Wieczorek 1995;Uchman & Myczyński 2006), even when this type of habitat was highly widespread GEOLOGICA CARPATHICA GEOLOGICA CARPATHICA GEOLOGICA CARPATHICA GEOLOGICA CARPATHICA GEOLOGICA CARPATHICA, 2013, 64, 5, 355-374 and recurrent in environments of the Tethys during the Early Jurassic.…”
Section: Introductionmentioning
confidence: 99%